Probing Covalency in the UO3 Polymorphs by U M4 edge HR- XANES. (May 2016) - Podkovyrina, Y; Pidchenko, I; Prüßmann, T; Bahl, S; Göttlicher, J.; Soldatov, A; Vitova, T
Abstract: Local atomic and electronic structure investigations of uranium trioxide (UO3 ) crystalline phases performed by the U M4 edge HR-XANES technique is presented. The experimental U M4 edge HR-XANES spectra of α-UO3, β-UO3 and γ-UO3 polymorphic phases are compared with spectra of uranate (CaU2 O7 ) and uranyl (UO3 1-2(H2 O)) compounds. We describe a finger print approach valuable for characterization of variations of U-O axial bond lengths. Theoretical calculations of spectra using full-multiple-scattering theory (FEFF9.6 code) are performed. We have tested and selected input parameters, which provide best agreement between experimental and calculated spectra.